Postbiotics as antioxidant and antimicrobial agents on the enhancement of growth performance, immunity, biomarker responses, meat quality and carcass characteristics in broilers under heat stress - Merzza, Humam Ali (2020)
Three experiments were conducted to study the effects of feeding postbiotics of L. plantarum on the performance of broiler chickens under heat stress. In vitro study was initially conducted to determine the antioxidant capacity and inhibitory activity against pathogens of six postbiotics (RG14, RG11, RI11, TL1, RS5, and UL4) obtained from different strains of Lactobacillus plantarum and then to select the best postbiotics based on the antioxidant activity. The 2,2-Diphenyl-1-Picryl-hydrazyl (DPPH) and 2,2'-azino-bis (3-thylbenzothiazoline-6-sulfonic) acid (ABTS) assays were used to examine the antioxidant activity of all postbiotics and ascorbic acid was used as standard antioxidant. The modified inhibitory activity (MAU) of the postbiotics was tested against pathogenic microorganisms such as Pediococcus acidilactici, Salmonella enterica, Escherichia coli, vancomycin-resistant enterococci (VRE) and Listeria monocytogenes. The oxytetracycline (OTC) was used as a positive control. The results indicated that all postbiotics showed activity to scavenging free radicals in both DPPH and ABTS assays. The RI11 demonstrated the highest scavenge of free radicals, followed by UL4, then RS5 as compared to other postbiotics (RG14, RG11 and TL1). All postbiotics (RI11, RS5 and UL4) had higher MAU/mL than OTC against all indicator organisms except VRE. Among the postbiotics, there was no different in MAU/mL against E.coli, VRE and L. monocytogenes. Postbiotic RS5 had higher inhibition activity against P. acidilactici and Salmonella than UL4, whereas RS5 was not different with RI11. Postbiotics RS5 and RI11 had higher optical density and lower pH, which corresponds to increase in inhibitory activity against indicator organisms. The results of the present study showed that postbiotics (RI11, RS5 and UL4) have the highest ability to scavenge free radicals and prevent the proliferation of pathogenic bacteria and thus chosen for evaluation in the following in vivo study. A feeding trial was then conducted to examine the effect of postbiotics on growth performance, nutrient digestibility, gut microbial population and histology, immune status, acute phase proteins and HSP70, antioxidant activity, meat quality and gene expression related to growth in broilers under heat stress. A total of 252 one-day-old male broiler chicks (Cobb 500) were randomly assigned in cages in identical environmentally controlled chambers. During the starter period from 1 to 21 days, all the birds were fed the same basal diet. On day 22, the birds were weighed and randomly divided into six treatment groups and exposed to cyclic high temperature at 36 ± 1 °C for 3 h per day from 11:00 to 14:00 until the end of the experiment. From day 22 to 42 (finisher period), an equal number of birds were subjected to one of the following diets: NC (negative control) basal diet; OTC (positive control) basal diet + 0.02% oxytetracycline; or AA (ascorbic acid) basal diet + 0.02% ascorbic acid. The other three groups (RI11, RS5 and UL4) were basal diet + 0.3% different postbiotics. The results demonstrated that birds fed RI11 diets had higher final body weight, total weight gain and average daily gain than the birds that received the NC, OTC and AA treatments. The feed conversion ratio was higher in the RI11 group compared with other groups. Dry matter (DM), organic matter (OM) and crude protein (CP) digestibility increased in broilers fed postbiotics RI11 and UL4 compared to NC and OTC groups. Carcass parameters were not affected by the postbiotic-supplemented diet. Postbiotic supplementation improved villi height in the duodenum, jejunum and ileum compared to the NC, OTC and AA treatments. The crypt depth of the duodenum and ileum was higher in NC group compared to other treatment groups except RI11 in duodenum, and UL4 in ileum was not different with NC groups. The villus height to crypt depth ratio of duodenum and ileum was higher for the postbiotic treatment groups and AA than the OTC and NC treatment groups. The postbiotic RI11 group recorded higher caecum total bacteria and Lactobacillus counts and lower Salmonella count compared to the NC and OTC treatment groups. The Bifidobacterium population in the NC group was lower compared to the other treatment groups. The postbiotic (RI11, RS5 and UL4) and AA treatment groups showed lower Enterobacteriaceae and E. coli counts and caecal pH than the NC and OTC treatment groups. The plasma immunoglobulin M (IgM) level was higher in the birds receiving postbiotic RI11 than those receiving other treatments. The plasma immunoglobulin G (IgG) level was higher in the RI11 treatment group than in the NC, AA and RS5 groups. The plasma immunoglobulin A (IgA) level was not affected by postbiotic supplements. Addition of postbiotics especially RI11 in broiler diets reduced plasma concentration of the α1-AGP (alpha1-acid glycoprotein) and CPN (ceruloplasmin) compared to other groups. The plasma T-AOC, CAT and GSH concentration was higher in RI11 and UL4 groups compared to other groups. The meat MDA (malondialdehyde) level for lipid peroxidation was lower in postbiotics and AA groups than NC and OTC groups. Feeding RI11, RS5 and UL4 decreased drip loss, cooking loss and shear force of breast meat compared to other groups. The RI11 increased the meat pH and decreased L* and b* as compared to NC and OTC groups. However, there was no difference between postbiotics and AA in meat pH, shear force and L* colour. The hepatic GHR mRNA expression level was increase in birds fed postbiotics RI11, RS5 and UL4, AA and OTC compared to the NC-fed birds. Postbiotic RI11 led to higher hepatic IGF-1 mRNA expression level compared to the NC, OTC, and AA treatments. Mortality was not significantly different among all the treatments. In conclusion, among the postbiotics applied in the current study as compared with NC, OTC and AA, postbiotic produced from L. plantarum RI11 could be used as a potential alternative to antibiotic growth promoter and source of antioxidant in the poultry industry. The subsequent feeding trial was conducted to examine the effects of feeding different levels of postbiotic RI11 on growth performance, digestibility, intestinal histomorphology, gut microbiota, lipid profile, antioxidant enzyme activity, immune response, meat quality, acute phase proteins and HSP70 mRNA expression, gene expression of mucosal immunity and intestinal barrier function and growth hormones in broilers under heat stress. In this experiment, the same animals, environment and management as described in previous experiment. The birds were fed on the following diets: 0.0% (negative control) basal diet; OTC (positive control) basal diet + 0.02% oxytetracycline; AA (ascorbic acid) basal diet + 0.02% ascorbic acid. Four further groups were the basal diet + (0.2%, 0.4%, 0.6% and 0.8%) postbiotic RI11 of the respective levels. Supplementation of 0.4%, 0.6% and 0.8% RI11 increased final body weight, total weight gain, average daily gain, digestibility of DM, CP, EE (ether extract) and better FCR than the birds fed the 0.0% RI11, OTC and AA treatments. Increasing the level of postbiotic RI11 in diet increased growth performance, nutrient digestibility, FCR, EE digestibility, total bacteria and Bifidobacterium population and decreased ceacal pH, E.coli and Clostridium population. Supplementation of different levels of postbiotic RI11 increased beneficial bacteria population, villi height, VH: CD (Villi height: crypt depth) ratio in the duodenum, jejunum and ileum, increased plasma glutathione peroxidase (GPx), catalase (CAT) and glutathione (GSH) enzyme activity, plasma IgM and mucosal IgA concentration, and reduced pathogen load, intestinal crypt depth, decreased MDA concentration of meat, decreased plasma α1- AGP and CPN concentration as compared to negative control and OTC groups. Feeding various dosage of postbiotic RI11 decreased the drip loss, cooking loss, shear force, lightness and yellowness of breast meat, increased the pH of meat, decreased total cholesterol, triglyceride, low-density lipoprotein (LDL) and very low-density lipoprotein (VLDL) as compared to 0.0% RI11 and OTC groups. However, no difference was observed in blood HDL, meat redness, OM and ash digestibility and plasma IgG levels. Different levels of RI11 in broiler diets showed improvement in meat quality after 7 days storage period and decreased MDA level as compared to negative and OTC groups. Postbiotic RI11 groups increased the mRNA expression of hepatic IGF-1, GHR, IL-10 and decreased of IL-8, TNF, HSP70 and α1-AGP levels compared to the negative control and OTC groups. Postbiotics also improved the integrity of the intestinal barrier by the upregulation of ZO-1 and MUC2 mRNA expression. However, no difference was observed in CLDN1 expression, but downregulation for OCLN expression in birds fed RI11 as compared with the 0.0% RI11. Supplementation of postbiotic RI11 in different levels quadratically increased the villi height, duodenum VH:CD ratio, plasma GPx, CAT and GSH activities, mucosal IgA and plasma IgM concentration, IGF-1, GHR, IL-10, MUC2 and ZO-1 mRNA expression, and reduced intestinal crypt depth, cholesterol profile, plasma CPN level, IL-8, TNF, α1-AGP and HSP70 mRNA expression. Supplementation of postbiotic RI11 at level 0.6% was sufficient to achieve the improvement in health and growth performance of broiler chickens under heat stress as compared to other levels. In conclusion, the results suggested that 0.6% (v/w) of postbiotic produced from L. plantarum RI11 could be a prospective alternative to the antibiotic as a growth promoter and antioxidant additives in the poultry industry.